INTELLECTUAL AGENT OF VERIFICATION OF TAKING INTO ACCOUNT INFORMATION OF THE SUBJECT DOMAIN IN THE PROCESS OF DEVELOPING SOFTWARE SYSTEMS - LOPATTO, IVAN; HOVORUSHCHENKO, TETIANA; KAPUSTIAN, MARIIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
When developing software systems, there is a gap in knowledge about the characteristics of the future software system. This gap is due in part to the partial consideration or non-consideration of information in the subject area during the life cycle of the software system. The size of the knowledge gap is not constant during the life cycle of the software system - the emergence of new information in the subject area may increase or decrease the size of the knowledge gap, depending on the degree of its consideration. For further successful implementation and use of the software system, it is desirable to reduce the size of the knowledge gap, taking into account as much information of the subject area during its life cycle. Therefore, fundamentally new approaches are needed, taking into account the information of the subject area in the process of software development of computer systems. The article analyzes the known intellectual agents, which showed that well-known intelligent agents do not solve the problem of verifying the consideration of information in the subject area in the development of software systems, so it is necessary to develop a concept of such an intelligent agent. Therefore, the article proposes the concept of an intellectual agent of verification of taking into account information of the subject domain in the process of developing software systems, which is based on the comparison of ideal and real ontologies, which contain the necessary and available information at each stage of the software life cycle. Such a pairwise comparison of relevant ontologies will make it possible to see the loss of information at each stage of the life cycle, as well as to estimate their volume. The perspective directions of future authors’ work: development of basic ontologies for all documents at each stage of the software system life cycle - based on relevant standards, guidelines, etc .; modeling and development of a method of activity of the intellectual agent of verification of the account of the information of subject branch in the course of development of software systems; implementation of an intelligent agent for verifying the consideration of information in the subject area in the process of developing software systems.